Utilisation and associated factors in public health centres in urban areas, Banten-Indonesia - Sasmito, Priyo; Sumartini, Sri; Ahmadi, Ahmadi; Purwanti, Nunuk Sri; Librianty, Nurfanida; Madani, Ultra; Nugroho, Kurnia Arik; Gayatri, Sri Wahyuni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Public Health Centers (PHCs) in urban areas face various challenges, including competition from numerous other health facilities. Purpose: To analyze the internal factors influencing the utilization of a PHC in Serang City, Banten. Method: The study is analytical observational research with a cross-sectional design. The population includes individuals aged 14 and older residing within the PHC service area. Data on age, education level, employment, insurance ownership, availability of health workers, accessibility, and perception of illness were collected. The outcome measured was the utilization of PHC services, and data were analyzed descriptively. Results: A total of 96 respondents participated in the study. Most respondents were male (49/51.0%), aged 14-44 (59/61.5%), had a senior high school education and higher (37/38.5%), worked in the formal sector (56/58.3%), had national insurance (78/81.3%), and held a positive perception of illness (86/89.6%). Additionally, the majority found PHC access easy (78/81.3%) and believed that the necessary health workers were available (78/81.3%). Statistical analysis revealed that education (p-value 0.00), employment (p-value 0.00), insurance ownership (p-value 0.00), availability of health workers (p-value 0.00), accessibility (p-value 0.00), and perception of illness (p-value 0.00) were all significantly related to PHC utilization. Conclusion: To improve the development of more effective health policies, further studies are needed regarding the mechanisms behind the influence of these factors.